Design and synthesis of novel 2-(indol-5-yl)thiazole derivatives as xanthine oxidase inhibitors. Issue 6 (15th March 2015) - Song, Jeong Uk; Choi, Sung Pil; Kim, Tae Hun; Jung, Cheol-Kyu; Lee, Joo-Youn; Jung, Sang-Hun; Kim, Geun Tae
Graphical abstract Compound 6k exhibits potent in vitro activities in xanthine oxidase inhibition (IC50 = 3.5 nM). It shows good oral availability and in vivo efficacy in treating hyperuricemic rats.